Variable Transcriptional Regulation of the Human Aldosterone Synthase Gene Causes Salt-Dependent High Blood Pressure in Transgenic Mice. (February 2015) - Mopidevi, Brahmaraju; Kaw, Meenakshi K.; Puri, Nitin; Ponnala, Madhusudan; Jain, Sudhir; Rana, Anita; Keetha, Narsimha R.; Khuder, Sadik A.; Fiering, Steven N.; Kumar, Ashok
Abstract : Background—: Aldosterone, synthesized in the adrenal cortex by the enzyme CYP11B2, induces positive sodium balance and predisposes to hypertension. Various investigators, using genomic DNA analyses, have linked -344T polymorphism in the human CYP11B2 (h CYP11B2 ) gene to human hypertension. h CYP11B2 gene promoter has 3 single-nucleotide polymorphisms in linkage disequilibrium: T/A at -663, T/C at -470, and C/T at -344. Variants ACT occur together and form the haplotype-I (Hap-I), whereas variants TTC constitute Hap-II. We hypothesize that these single-nucleotide polymorphisms, when present together, will lead to haplotype-dependent differences in the transcriptional regulation of the h CYP11B2 gene and affect blood pressure regulation. Methods and Results—: We evaluated differences in tissue expression in vivo and consequential effects on blood pressure stemming from the 2 haplotypes. Novel transgenic mice with the h CYP11B2 gene, targeted to the mouse HPRT locus, with either Hap-II or Hap-I variant are used in this study. Our results show increased adrenal and renal expression of h CYP11B2 in transgenic mice with Hap-I when compared with mice with Hap-II. Importantly, we observed increased baseline blood pressure in Hap-I transgenic mice, an effect accentuated by a high-salt diet. Pathophysiological effects of elevated aldosterone were corroborated by our results showing upregulation of proinflammatory markers in renal tissues from the transgenic mice with Hap-I. Conclusions—: These findings characterize the haplotype-dependent regulation of the h CYP11B2 gene where -344T serves as a reporter polymorphism and show that Hap-I leads to increased expression of h CYP11B2, with permissive effects on blood pressure and inflammatory milieu. Abstract : Supplemental Digital Content is available in the text.